Alkylammonium Modified Photosensitizers Achieve Lysosome-Precision Photodynamic Therapy: Implications from Molecular Dynamics Simulations - He, Xi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Photodynamic therapy (PDT) is one of the developing treatment modalities that has been clinically approved for cancer treatment. It uses an organic photosensitizer that harnesses the light energy and converts intracellular oxygens to reactive cytotoxic species. The resulting chemicals can then damage cells and lead to cancer cell death. However, the existing photosensitizers do not show cancel cell or organelle specificity, which lowers their treatment outcomes. In this project, we used molecular dynamic simulations to demonstrate that a straightforward alkylammonium modification on photosensitizers is able to endow conventional photosensitizers with the ability to target and accumulate in lysosomes. This acquired lysosome specificity may achieve the lysosome-precision PDT experimentally, which is expected to enhance the PDT outcomes. More importantly, such organelle-precision modifications have the potential to be extended beyond PDT treatment and make contribution to drug discovery and eventually cancer treatment.